Model for developing audio visual media efforts to increase religion and moral values of early age children kota Bengkulu - Margaretha, Lydia (Program Studi Akuntansi IKOPIN, 2022)
This study aims to: (1) Design audio-visual media development that can enhance religious and moral values in learning; (2) Describe the effectiveness of using audio-visual media to improve religious and moral values. The subjects of this study were class B teachers and children in the B grade of Bengkulu City. While the object of this research is audio-visual media as a learning medium in aspects of religious and moral values. This research was carried out using a